Interacting with technology to interact physically: Investigating affordances of tabletops to facilitate collaboration for conflicting users - Hansen, Preben; Loizides, Fernando; Ioannou, Andri (My University, 2016)
In this work, we investigated the affordances of tabletops in order to begin testing them within a specialised and sensitive collaborative learning environment; namely, that with users in conflict. We utilised a bespoke prototype application named ‘IdeaSpace’ which makes use of multi-touch interactive tabletop technology and is specifically designed to encourage user collaboration. We tested the usability and interaction with a group of users as a pilot test, followed by a second test in a shared space with crowds of users serendipitously using the tabletop in an open, public space. From the tests we identified and isolated findings directly relating to collaboration elements needing attention before introducing IdeaSpace to participants in conflict.
Keywords: Collaboration; Conflict; Tabletop technology